Generalized Common Fixed Point Results via Greatest Lower Bound Property. (10th July 2014) - Kutbi, Marwan Amin; Ahmad, Jamshaid; Azam, Akbar; Al-Rawashdeh, Ahmed Saleh
Abstract : The aim of this paper is to unify the concept of greatest lower bound (g.l.b) property and establish some generalized common fixed results. We support our results by a nontrivial example.